The Legal Battle over Telecommunications Service Classification in the U.S.: From Network Neutrality to Voice-Over-Internet Protocol Service - Barbara A. Cherry (International Telecommunications Society (ITS), 2021)
In the U.S., network neutrality policy has been on a trajectory of escalating political instability since the early 2000's. As explained in Cherry (2020), this trajectory can be understood as a microcosm of the more general trajectory of political dysfunction under U.S. governance that coincides with the era of deregulatory policymaking. Under U.S. governance, adversarial legalism - that is, lawyer-dominated litigation - has evolved as a means of policymaking in the U.S., the role of which has intensified with the rise of divided government and party polarization. The federal Telecommunications Act of 1996 was enacted during the waning period of bipartisan negotiation of the 1990's, and its implementation has been left to a heightened period of adversarial legalism under hyperpartisanship between the Republican and Democratic political parties. As a result, the instability of U.S. network neutrality policy is reflective of the current phase of hyperpartisanship within a process of adversarial legalism. [...] This paper expands upon my prior research regarding U.S. deregulatory telecommunications policies (Cherry, 1999, 2003, 2006, 2010, 2015, 2020) to discuss the importance of the I-VOIP litigation, in both the U.S. and the international community. Under U.S. law, its importance arises from legal flaws in the 8th Circuit Court ruling in Charter Advanced Services v. MPUC and the resultant legal confusion as to the scope of federal preemption of state law. It is also the manifestation of yet another step in the trajectory of political instability and flawed legal analyses in U.S. telecommunications policy, distorting the economic and technical evolution of U.S. telecommunications markets. The consequences, however, will not be confined to the U.S. but will likely diffuse to international markets as well. Moreover, understanding these developments in the U.S. can serve as a case study for identifying how political instability in other nations may be distorting telecommunications regulation, markets and technology. International regimes, in turn, may require further evolution in recognition of nations' political instability on global telecommunications.
Keywords: 330